EVALUASI CACAT PENGERINGAN DAN PEMESINAN PADA EMPAT JENIS KAYU CEPAT TUMBUH TERMODIFIKASI PANAS - Ulfa Adzkia; Trisna priadi; Lina Karlinasari (Jurnal Penelitian Hasil Hutan, 2025)
Heat treatment is one method that can improve the quality of wood including for fast-growing wood species. However, this treatment can cause some drying defects as well as the change of machining properties after applying that heat treatment. The purpose of this study was to evaluate the effect of wood species and heating time on the drying and machining defects. The fast-growing wood species used were teak, mangium, jabon, and sengon. The heat treatment was carried out at a temperature of 165°C with variation in time were 0 (control), 2, and 6 hours. The result showed that the moisture content and wood density decreased after heat treatment. Heat treatment was succeeded to decrease the moisture content of 57% and caused a decreasing of density until 20% compared with control wood. The drying defects of end checks in teak, mangium, jabon and sengon increased after 2 and 6-hour heat treatment. In the other hand, the surface checks defect of teak, mangium, sengon and jabon were decreased. The defects after applying machining activities i.e. the defects of sanding, planing, shaping, and boring were decreased in teak, mangium, jabon and sengon after heat treatment of 2 and 6-hour. Jati was the best wood species in term of machining quality followed by jabon, mangium, and sengon after heat treatment. At the temperature of 165°C in 2 hours could be considered as the appropriate time for heat treatment in term of obtaining minimal defects of drying and machining.